2019
DOI: 10.1002/app.48666
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory and self‐healing behavior of styrene–butadiene–styrene/ethylene‐methacrylic acid copolymer (SBS/EMAA) elastomers containing ionic interactions

Abstract: Ionic interactions were introduced to styrene-butadiene-styrene (SBS) through blending with ethylene-methacrylic acid copolymer (EMAA) and zinc oxide (ZnO), and a following in situ neutralization reaction between the carboxyl groups of EMAA and ZnO. The resultant SBS/EMAA (60/40 wt %) blends containing zinc carboxylate crosslinks exhibited high modulus and strong long-time relaxation characteristics. With 74% of the carboxyl groups neutralized (zinc cation fraction of 1.7 wt %), the tensile strength of the ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…After heat treatment at 130 • C for 30 min, the residual strains were 100% recovered for all samples. However, the dissipating energy did not completely recover, and the recovery ratios of the stress at 200% extension and the dissipating energy increased sequentially from mEVA to DA1 to ZnMA 10 wt % to DA1-ZnMA 10 wt %, which was different from the results of SBS/EMAA blends [34], in which the irreversible deformation at large strain was due to the introduction of the crystalline EMAA. For ZnMA 10 wt % and DA1-ZnMA 10 wt %, the stresses at 200% extension were completely recovered attributed to excellent recovery ability of these reversible crosslinks.…”
Section: Discussioncontrasting
confidence: 76%
“…After heat treatment at 130 • C for 30 min, the residual strains were 100% recovered for all samples. However, the dissipating energy did not completely recover, and the recovery ratios of the stress at 200% extension and the dissipating energy increased sequentially from mEVA to DA1 to ZnMA 10 wt % to DA1-ZnMA 10 wt %, which was different from the results of SBS/EMAA blends [34], in which the irreversible deformation at large strain was due to the introduction of the crystalline EMAA. For ZnMA 10 wt % and DA1-ZnMA 10 wt %, the stresses at 200% extension were completely recovered attributed to excellent recovery ability of these reversible crosslinks.…”
Section: Discussioncontrasting
confidence: 76%
“…The former mainly includes DA chemistry, [ 15–17 ] disulfide bonds, [ 18–20 ] imine bonds, [ 21,22 ] boron‐based bonds. [ 23–25 ] The latter mainly refers to hydrogen bonding, [ 26–29 ] host‐guest interactions, [ 30–32 ] ionic interactions, [ 33,34 ] and metal‐ligand interactions. [ 11,35–37 ]…”
Section: Introductionmentioning
confidence: 99%
“…20,[23][24][25] As emphasized, EMAA is one of the most studied ionomers with healing abilities. 1,21,26,27 In their works, Kalista et al 19 studied the self-healing of EMAA in ballistic tests and have observed that the incorporation of aliphatic carboxylic acids into EMAA increased the elastomeric behavior and elastic healing of the samples due the change of the ionomeric clusters mobility. Moreover, those authors observed that, when the ionic clusters were plasticized, the rate of recovery was increased, and the behavior was attributed to the reestablishment of ionic clusters through the reorganization of Coulombian interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As emphasized, EMAA is one of the most studied ionomers with healing abilities 1,21,26,27 . In their works, Kalista et al 19 studied the self‐healing of EMAA in ballistic tests and have observed that the incorporation of aliphatic carboxylic acids into EMAA increased the elastomeric behavior and elastic healing of the samples due the change of the ionomeric clusters mobility.…”
Section: Introductionmentioning
confidence: 99%